Effectiveness of Police Organizational Performance in Tackling and Preventing Drug Abuse in Indonesia - Farizky, Vonny; Putranti, Ika Riswanti; Kismartini, Kismartini; Wijayanto, Wijayanto (Jurnal Ilmu Sosial Mamangan, 2024)
Effectiveness shows the success of achieving the goals that have been set. If the results of activities are closer to the target, it shows the higher the effectiveness. An organization is considered to achieve high effectiveness if the it is free from various characteristics of ineffectiveness. This research aims to analyze the effectiveness of the Indonesian police organization in tackling drug abuse that occurs in society today. In accordance with the Function, Purpose, Position, Role, and Authority of the Police, which is very large and important to prevent drug trafficking and abuse in Indonesia, it has been written in Law Number 2 of the Year concerning the Indonesian National Police. The results indicated that the effectiveness of police organizational performance in tackling and preventing drug abuse in Indonesia is currently not optimal. This is shown in the yearly prevalence rate of drug abuse, which increased by 0,15% from 1,80% in 2019 and to 1,95% in 2021. This increase is quite large when viewed from the total population, drug abuse. This is estimated at 3.662.646 people aged 15-64 years over the past year shows an increase of 243.458 people compared to 2019 (3.419.188 people). Meanwhile, the prevalence rate of ever-use drug abuse increased by 0,17% from 2,4% in 2019 to 2,57%. With an absolute number in 2021 of 4.827.616 people aged 15-64 years having used drugs, this number is 292.872 more people than in 2019 (4.534.744 people). With the increase in narcotics crimes in the Provinces, Districts/Cities throughout Indonesia, the Police, assisted by the community, needs to be more active in carrying out preventive measures that can narrow the space for perpetrators who will commit narcotics crimes.